ANALISIS KASUS PERBUDAKKAN DI ATAS KAPAL PENANGKAP IKAN ASAL CHINA KEPADA SEKELOMPOK PEKERJA INDONESIA DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL - Maramba, Umbu Frenly Y; Kase, Dhesy A (Petitum Law Journal, 2026)
This article analyzes the practice of modern slavery experienced by Indonesian crew members aboard the Chinese-flagged fishing vessel Long Xing 629, which involved forced labor, violence, document confiscation, and burial at sea without family consent. This study employs a normative legal method using statutory, conceptual, and case approaches. It focuses on how international legal instruments such as ILO Convention No. 29, ILO Convention No. 188, the 2000 Palermo Protocol, and UNCLOS 1982 regulate the protection of migrant workers in the maritime sector and establish the responsibilities of both flag states and countries of origin. The findings reveal that weak enforcement of the genuine link principle and abuse of the flag of convenience system have exacerbated slavery practices at sea. Furthermore, enhanced inter-state cooperation, domestic legal reform, and international collaboration are crucial to strengthening legal protection and preventing future exploitation.